Stray dogs and their relationship with the public road pollution in Huaraz city, Ancash-Perú-2017 - Aliaga Zegarra, Edell (2019)
Currently, irresponsible dog ownership is perceived, we observe a lot of these wandering on publicroads in cities, Huaraz is no stranger to this problem, the dogs cause discomfort, forming packs thatattack people, spread garbage, litter the streets , parks and gardens with urine and feces, which aresprayed and dispersed in the air causing diseases. The objective was to determine the relationship betweenstray dogs and pollution of public roads in the city of Huaraz, Ancash - Peru 2017. Correlationstudies, doing: Counting of dogs, being the population and sample all dogs; survey to family heads,population and sample 7460 and 366 dwellings respectively; coprological analysis, population all fecesand sample 153 fresh feces for convenience in the six neighborhoods. In addition, municipal andhealth authorities were interviewed. A total of 1239 stray dogs were determined; 76, 0 % of all surveyedraised dogs with a p value of 0, 000 indicating a signicant relationship between stray dogs andpollution of public roads, it was found that 15, 7 % of Ancylostoma spp, 3, 3 % of Diphilidiun caninumand 1, 3 % of Giardia spp by the method of direct observation andWillis